Systematic Literature Review: Efektifitas Model Pembelajaran Realistic Mathematics Education terhadap Kemampuan Pemecahan Masalah Matematis di SD - Olga Yani Aruan; Petrus Weli Darman Waruwu; Taruli Marito Silalahi; Asmawenti Laia (Journal on Education, 2025)
The purpose of this study is to examine the effectiveness of the Realistic Mathematics Education (RME) learning model in improving students' ability to solve mathematical problems. This ability reflects the level of students' expertise in formulating solutions to the mathematical problems they encounter. RME is a learning approach that transforms abstract mathematical concepts into more concrete ones through everyday contexts. The method used in this study is a Systematic Literature Review, which involves analyzing relevant literature to address the research focus. This study involves analyzing 15 scientific articles published between 2017 and 2024. The findings of this study indicate that the RME approach can enhance students' problem-solving abilities by connecting learning materials to real-world contexts, encouraging active student participation in the learning process, and developing critical and creative thinking skills.